2018
DOI: 10.2147/idr.s173624
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characteristics of methicillin-resistant and methicillin-susceptible <em>Staphylococcus aureus</em> isolated from pigs: implication for livestock-association markers and vaccine strategies

Abstract: BackgroundRoutine non-therapeutic antimicrobial use and overcrowding in animal farming may facilitate the propagation of methicillin-resistant Staphylococcus aureus (MRSA). This study aimed to examine the carriage prevalence and phenotype–genotype characteristics of MRSA and methicillin-susceptible S. aureus isolated from pigs.MethodsNasal swabs were collected from 1,458 pigs in 9 pig farms and 3 slaughterhouses. All strains were tested for antimicrobial susceptibility, resistance genes, and virulence genes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 57 publications
7
23
1
Order By: Relevance
“…As in our study, in other studies reporting the presence of CC97 MRSA, the isolates are frequently multidrug resistant with resistance only to β-lactams and tetracyclines but also to macrolides, lincosamides and aminoglycosides [17,31]. Although the relationship between antibiotic resistance profiles and clonal complexes is still not clear, some studies suggest that different LA-MRSA clones may present specific resistance patterns [42]. Macrolide-lincosamide-streptogramin (MLS) resistance occurs by the cross-resistance among these antibiotics, and bacteria with resistance to MLS were previously reported to be transmitted from animals to humans through the food chain [43].…”
Section: Characterization Of Cc97 Mrsa Isolatessupporting
confidence: 66%
“…As in our study, in other studies reporting the presence of CC97 MRSA, the isolates are frequently multidrug resistant with resistance only to β-lactams and tetracyclines but also to macrolides, lincosamides and aminoglycosides [17,31]. Although the relationship between antibiotic resistance profiles and clonal complexes is still not clear, some studies suggest that different LA-MRSA clones may present specific resistance patterns [42]. Macrolide-lincosamide-streptogramin (MLS) resistance occurs by the cross-resistance among these antibiotics, and bacteria with resistance to MLS were previously reported to be transmitted from animals to humans through the food chain [43].…”
Section: Characterization Of Cc97 Mrsa Isolatessupporting
confidence: 66%
“…Erythromycin is known to act by inhibition of protein synthesis. Several authors have also reported similar findings about Staphylococcus aureus from clinical samples showing resistance of different degrees [35][36][37]. According to Adekanmbi, Falodun antimicrobial resistance may be plasmid-coded and this may encourage transfer of the resistance genes to once-susceptible microorganism.…”
Section: Discussionmentioning
confidence: 73%
“…In this study, we investigated the prevalence of S. aureus in different food producing animals, including pigs, cattle, goats, rabbits and chicken, in Chongqing, China. To our understanding, this is the first comprehensive survey on livestock-associated S. aureus in Chongqing, although numerous epidemiological studies of this organism have been carried out in other regions of China [1,29,30], and a report about S. aureus isolated from goats in Chongqing [31] has been published. The average prevalence of S. aureus in our study was similar with those obtained from Jiangmen, China [30], but differed from other areas.…”
Section: Discussionmentioning
confidence: 99%
“…To our understanding, this is the first comprehensive survey on livestock-associated S. aureus in Chongqing, although numerous epidemiological studies of this organism have been carried out in other regions of China [1,29,30], and a report about S. aureus isolated from goats in Chongqing [31] has been published. The average prevalence of S. aureus in our study was similar with those obtained from Jiangmen, China [30], but differed from other areas. For instance, a study carried out in Henan showed that 23.7% of animal samples collected from cows, swine, chicken and ducks, were positive for S. aureu [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation